Vicious cycle of oxidative stress and neuroinflammation in pathophysiology of chronic vascular encephalopathy - Dmytriv, Tetiana R.; Duve, Khrystyna V.; Storey, Kenneth B.; Lushchak, Volodymyr I. (Frontiers in Physiology, 2024)
Chronic vascular encephalopathy (CVE) is a frequent cause of vascular mild cognitive impairment and dementia, which significantly worsens the quality of life, especially in the elderly population. CVE is a result of chronic cerebral hypoperfusion, characterized by prolonged limited blood flow to the brain. This causes insufficient oxygenation of the brain leading to hypoxia. The latter can trigger a series of events associated with the development of oxidative/reductive stresses and neuroinflammation. Addressing the gap in knowledge regarding oxidative and reductive stresses in the development of vascular disorders and neuroinflammation can give a start to new directions of research in the context of CVE. In this review, we consider the hypoxia-induced molecular challenges involved in the pathophysiology of CVE, focusing on oxidative stress and neuroinflammation, which are combined in a vicious cycle of neurodegeneration. We also briefly describe therapeutic approaches to the treatment of CVE and outline the prospects for the use of sulforaphane, an isothiocyanate common in cruciferous plants, and vitamin D to break the vicious cycle and alleviate the cognitive impairments characteristic of patients with CVE.